Case Report: Primary urethral repair in a cat secondary to urethral tear sustained during the catheterization procedure - Hankins, Kimery L.; Zacher, Laurie A. (Frontiers in Veterinary Science, 2025)
This report describes a case of primary urethral repair secondary to a urethral tear in a 4-year-old, male castrated, domestic shorthair cat. The cat was initially presented on an emergency basis for complete urethral obstruction with radiographic evidence of cystolithiasis. A perineal urethrostomy and concurrent cystotomy were performed to relieve the urethral obstruction and retrieve the uroliths. One day postoperatively, a uroabdomen secondary to a urethral tear was diagnosed. An indwelling Foley catheter was placed. A contrast cystourethrogram performed 4 days later, however, revealed a persistent urethral tear, so a Foley catheter was replaced. Seven days after replacement, another contrast cystourethrogram was performed revealing a persistent urethral tear. Due to the anatomic location of the tear identified on radiographs after the contrast study, primary closure of the urethral defect with the placement of a Foley urinary catheter was completed. Another contrast urethrogram 7 days after repair revealed a resolved defect with no leakage appreciated once the urinary catheter was removed. This case highlights the management, surgical techniques, and success of a primary urethral repair in a cat. It demonstrates successful outcomes and follow-up for an uncommon procedure and illustrates the importance of initial catheterization for blocked felines.